Cross-cohort multi-omics analysis identifies novel clusters driven by EMT signatures in colorectal cancer - Wu Ning; Wenqing Jia; Jingyuan Ning; Lei Zhou; Zongze Li; Lin Zhang; Xin Song (Frontiers in Immunology)
IntroductionThe pronounced heterogeneity of colorectal cancer (CRC) significantly impacts patient prognosis and therapeutic response, making elucidation of its molecular mechanisms critical for developing precision treatment strategies. This study aimed to systematically characterize tumor cell heterogeneity and explore its clinical implications.MethodsFive single-cell RNA sequencing cohorts were integrated (comprising 70 CRC samples and 164,173 cells) to systematically analyze tumor cell heterogeneity. Unsupervised clustering analysis based on VEGFR+ tumor cell signature genes was used to stratify CRC patients. Key molecular mechanisms were validated through in vitro cellular experiments, in vivo animal models, molecular docking, and dynamics simulations.ResultsThe analysis successfully identified five distinct tumor cell subtypes, with the VEGFR+ subtype exhibiting marked epithelial-mesenchymal transition (EMT) activation signatures and strong association with metastasis and poor clinical outcomes. Based on VEGFR+ signature genes, CRC patients were stratified into three subgroups: C1 (metabolically active), C2 (proliferative), and C3 (invasive), with the C3 subtype demonstrating high metastatic potential, stem-like properties, and an immunosuppressive microenvironment, along with a five-year survival rate below 50%. Mechanistic investigations identified HOXC6 as a key driver of the C3 subtype, with HOXC6 knockout significantly suppressing CRC cell proliferation, migration, and invasion. Furthermore, molecular docking revealed that the targeted agent abemaciclib effectively binds HOXC6, with both cellular and animal experiments confirming its ability to inhibit CRC cell functions and significantly reduce tumor burden in nude mice.DiscussionThis study establishes the first single-cell-resolution molecular classification system for CRC, delineates the mechanistic link between EMT subtypes and metastatic progression, and identifies HOXC6 as a novel therapeutic vulnerability. These findings provide a translational foundation for precision oncology and offer new rationale for precision diagnosis and treatment of colorectal cancer.